Circadian variation of in-hospital cardiac arrest. (November 2020) - Tripathi, Avnish; Girotra, Saket; Toft, Lorrel E. Brown; ,
Abstract: Background: Out of hospital cardiac arrests, especially those due to ventricular tachyarrhythmias, have higher incidence in the morning. It is unknown whether in-hospital cardiac arrests follow a similar pattern. Aim of the study: The purpose of this study was to analyze the circadian variation of in-hospital cardiac arrest incidence. Methods: This retrospective review of data from the multicenter Get With The Guidelines-Resuscitation registry between 2000 and 2014 used multivariable hierarchical logistic regression analysis to examine circadian rhythm of in-hospital cardiac arrest over a 24-h cycle, stratified by initial shockable versus non-shockable rhythm. Results: Among 154, 038 patients, initial rhythm was recorded as asystole or pulseless electrical activity (non-shockable) in 124, 918 (81%), and ventricular fibrillation or ventricular tachycardia (shockable) in 29, 120 (19%). Among non-shockable events, the highest relative proportion occurred during 0400−0759 (17.9%), followed by 0000−0359 (17.1%). For shockable rhythms the greatest relative proportion occurred between 2000−2359 (17.0%), followed by 1200−1559 (16.9%). Multivariable analysis showed that the relative risk of non-shockable compared to shockable arrest was slightly higher from midnight through 0359 (aOR 1.13; 95% CI 1.06–1.20, p < 0.001) and from 0400 through 0759 h (aOR 1.14; 95% CI 1.07−1.22, p < 0.001). Although statistically significant, the magnitude of difference in incidence by time of day was small in both groups. Conclusions: Although small differences in the relative frequency of in-hospital cardiac arrest (both shockable and non-shockable rhythms) were noted during different time intervals, in-hospital cardiac arrest occurs with nearly equal frequency throughout the day. Our findings have important implications for hospital staffing models to ensure that quality of resuscitation care is consistent regardless of time.